Hydro‐Assisted Self‐Regenerating Brominated N‐Alkylated Thiophene Diketopyrrolopyrrole Dye Nanofibers—A Sustainable Synthesis Route for Renewable Air Filter Materials. Issue 14 (17th March 2020) - Ravi, Sai Kishore; Singh, Varun Kumar; Suresh, Lakshmi; Ku, Calvin; Sanjairaj, Vijayavenkataraman; Nandakumar, Dilip Krishna; Chen, Yun; Sun, Wanxin; Sit, Patrick H.‐L.; Tan, Swee Ching
Abstract: With rising global concerns over the alarming levels of particulate pollution, a sustainable air quality management is the need of the hour. Air filtration research has gained momentum in recent years. However, the research perspective is still blinkered toward formulating new fiber systems for the energy‐intensive electrospinning process to fabricate high quality factor air filters. A holistic approach on sustainable air filtration models is still lacking. The air filter model presented in this work uses a simple process involving water‐induced self‐organization and self‐regeneration of nanofibers, and an easy recycling route after the filter life that not only facilitates reuse of the microfibrous scaffold holding the nanofibers but also allows renewal of nanofibers. Three generations of air filters are fabricated and tested, all having high particulate matter (PM)‐adsorbing tendency, high filtration efficiency (>95%), and high Young's modulus (≈5 GPa). The renewable air filters offer a sustainable alternative to the present cost‐intensive electrospun air filters. Abstract : A simple procedure involving water‐induced self‐organization and self‐regeneration of the nanofibers, followed by an easy recycling route after the filter life, not only enables reuse of the microfibrous scaffold holding the nanofibers but also allows renewal of nanofibers, a sustainable design by hydro‐assisted self‐regeneration of nanofibers.